Periapical Disease and the Prefrontal Cortex. Is there a Relationship between Calcium-Binding Protein and Neurodegenerative Diseases? - Tessarin, Gestter Willian Lattari; Santos, Rodrigo Martins dos; Pereira, Renato Felipe; Mattera, Maria Sara de de Lima Coutinho; Tsosura, Thais Veronica Saori (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Apical periodontitis (AP) or periapical lesion (PL) is an inflammatory disease that causes pain, loss of bone and destruction of other tissues of teeth support. This condition could be caused by caries, dental trauma and/or periapical microleakage wich is regulated by the immune system or inflammatory response. Several analyses have shown that endodontic infection can cause systemic alterations like stroke, insulin resistance, cardiovascular diseases and to contribute to the appearance of neurodegenerative disorders. The prefrontal cortex (PfC), positioned in the most anterior region of the brain, is essentially involved behavioral abilities, intellectual roles, cognition, learning and other functions. Neurons with laminar distribution in the PfC, especially in the lower layers express several types of calcium-binding proteins (CaBPs) like parvalbumin, calbindin and calretinin that are involved in calcium buffering into the brain (CNS). These proteins are co-localized with GABAergic neurons, main inhibitory cells into the brain. Piece of evidence has pointed out a relationship between apical periodontitis and neurodegenerative diseases where microorganisms and/or toxins produced in the teeth infection can penetrate the bloodstream, infiltrate the blood-brain barrier limit and active astrocytes and microglial cells in the central nervous system (CNS) and increase the releasing of pro-inflammatory cytokines promoting pyramidal and non-pyramidal neuronal degeneration. Thus, is there a relationship among apical periodontitis, oral hygiene and prefrontal cortex and neurodegenerative disorders?